Low‐Frequency Sub‐Terahertz Absorption in HgII−XCN−FeII (X=S, Se) Coordination Polymers. Issue 7 (10th January 2023) - Li, Guanping; Stefanczyk, Olaf; Kumar, Kunal; Mineo, Yuuki; Nakabayashi, Koji; Ohkoshi, Shin‐ichi
Abstract: Self‐assembly Fe II complexes of phenazine (Phen), quinoxaline (Qxn), and 4, 4′‐trimethylenedipyridine (Tmp) with tetrahedral building blocks of [Hg II (XCN)4 ] 2− (X=S or Se) formed six new high‐dimensional frameworks with the general formula of [Fe( L ) m ][Hg(XCN)4 ]⋅solvents ( L =Phen, m /X=2/S, 1 ; L =Qxn, m /X=2/S, 2 ; L =Qxn, m /X=1/S, 3 ; L =Qxn, m /X=1/Se, 3‐Se ; L =Tmp, m /X=1/S, 4 ; and L =Tmp, m /X=1/Se, 4‐Se ). 1, 3, and 3‐Se show an intense sub‐terahertz (sub‐THz) absorbance of around 0.60 THz due to vibrations of the solvent molecules coordinated to the Fe II ions and crystallization organic molecules. In addition, crystals of 1, 4, and 4‐Se display low‐frequency Raman scattering with exceptionally low values of 0.44, 0.51, and 0.53 THz, respectively. These results indicate that heavy metal Fe II −Hg II systems are promising platforms to construct sub‐THz absorbers. Abstract : A new series of high‐dimensional thiocyanate‐/selenocyanate‐bridged networks [Fe ( L ) m ] [Hg (XCN)4 ]⋅solvents ( L =phenazine/quinoxaline/4, 4′‐trimethylenedipyridine; X=S/Se) exhibits unique low‐frequency terahertz absorbance and Raman scattering spectra. The phonon‐mode analysis is supported by quantum chemical calculations, indicating the importance of heavy elements in these phenomena and demonstrating the potential of the ab initio method.